Radiopharmaceutical small-scale preparation in Europe: will we be able to harmonize the situation? - Estrella Moya; Celia Cerrato; Luis Miguel Bedoya; José Antonio Guerra (SpringerOpen, 2024)
Abstract Background Radiopharmaceuticals have been considered a special group of medicines in Europe since 1989. The use of radiopharmaceuticals that have marketing authorization should always be the first option in clinical use, however due to their special properties the availability of approved radiopharmaceuticals is limited. For this reason, they can be produced on a small scale outside the marketing authorization process. Main body The in-house radiopharmaceutical preparations represent an important source of these special medicines for routine nuclear medicine practice. However, a lack of harmonization in Member States' regulations leads to extreme differences in the use and availability of radiopharmaceuticals across Europe. The aim of this work is to provide an overview of the different national regulatory frameworks in which Directive 2001/83/UE is adopted on the preparation of radiopharmaceuticals outside the marketing authorization track in Europe. Nine different national regulations have been studied to describe how unlicensed radiopharmaceuticals are prepared. Special attention is paid to reflect the minimum standards that these preparations should meet as well as the educational requirements to be a radiopharmacist in charge of them. Conclusion The rapid development of new radiopharmaceuticals used in radiometabolic therapy requires a common regulation that allows balance between the use and preparation of licensed and unlicensed radiopharmaceuticals. The absence of a harmonized regulation for the radiopharmaceutical small-scale preparation and the implementation of Good Manufacture Practices, leads to extreme differences in the use, quality assurance and availability of radiopharmaceuticals in Europe.